2014
DOI: 10.1186/s12879-014-0645-6
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of exclusive breastfeeding against hand, foot and mouth disease

Abstract: BackgroundInfants who are exclusively breastfed receive natural protection against some infectious agents. This study examined whether there was protective effect of exclusive breastfeeding on the occurrence of hand, foot and mouth disease, which was an emerging infectious disease among children in China.MethodsA community-based case–control study was carried out among children age 4 years or younger in Guangdong Province, China. Cases were newly diagnosed hand, foot and mouth disease. Controls were randomly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 38 publications
2
14
1
Order By: Relevance
“…The study of Lin et al [28] supports this finding; children who had been breastfed for less than 6 months had a greater chance for HFMD infection than those who had been breastfed for more than 6 months. Zhang et al [29] reported that in a case-control study in China, breastfeeding was presented as a major factor for HFMD infection among young children.…”
Section: Discussionsupporting
confidence: 78%
“…The study of Lin et al [28] supports this finding; children who had been breastfed for less than 6 months had a greater chance for HFMD infection than those who had been breastfed for more than 6 months. Zhang et al [29] reported that in a case-control study in China, breastfeeding was presented as a major factor for HFMD infection among young children.…”
Section: Discussionsupporting
confidence: 78%
“…This may be because boys are more active than girls, and would therefore have more opportunity to be exposed to environments that contain the HFMD virus. Furthermore, studies have shown that breastfeeding has protective effects against HFMD [32], which may be why infants under one year of age have a lower incidence than children aged one to two years. In China, maternity leave is only four months, so children over the age of one year receive less protection via breast milk.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue could be a marker for central nervous system involvement. According to the epidemic of EV-A71 in Taiwan in 1998, central nervous system involvement first developed in the most severe cases, followed by circulatory system involvement1718. In the most severe cases, patients developed tachycardia and cyanosis within 2 to 5 days after onset of HFMD, and died within 12 to 18 hours after onset of these symptoms1920.…”
Section: Discussionmentioning
confidence: 99%